2022
DOI: 10.1007/s00402-022-04682-0
|View full text |Cite|
|
Sign up to set email alerts
|

Prediction of individual graft for anterior cruciate ligament reconstruction using anthropometric data

Abstract: Introduction Multiple options for individual anterior cruciate ligament (ACL) reconstruction exist; still, there are no guidelines for the preoperative preparation. The aim of this study was to assess the correlation between patients’ anthropometric data (height, weight, and age) and measurements of potential tendons (quadriceps-, patella, hamstrings tendon) for an anterior cruciate ligament reconstruction. Material and methods MR images of 102 patients ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Ideally, if we strive for patient specific ACL reconstruction, the native ACL should be reconstruction in all its shape and dimensions. A recent study has shown that anthropometric data can be used to predict the graft dimensions, by which means an appropriate graft can be selected preoperatively [ 24 ]. That way true anatomic ACL reconstruction may become within reach.…”
Section: Discussionmentioning
confidence: 99%
“…Ideally, if we strive for patient specific ACL reconstruction, the native ACL should be reconstruction in all its shape and dimensions. A recent study has shown that anthropometric data can be used to predict the graft dimensions, by which means an appropriate graft can be selected preoperatively [ 24 ]. That way true anatomic ACL reconstruction may become within reach.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate graft tensioning can result in excessive knee laxity, persistent instability, and the development of arthritis, while excessive graft tensioning may lead to loss of ROM in knee extension, graft failure, and improper positioning of tibia and femur. 31 , 32 Proper tension should be placed on the graft via the passing sutures, prior to placement of an interference screw to ensure graft remains adequately taut. Placement of the femoral interference screw ( Fig 5 ) should be done parallel to the tunnel, while the knee is in flexion, after which any laxity of the graft from the tibial tunnel can be removed through repetitive cycling of the knee.…”
Section: Graft Tensioning and Fixationmentioning
confidence: 99%
“…Anterior cruciate ligament reconstruction (ACLR) aims to restore the stability of the knee prior to rupture of the ACL [35]. The ideal graft option for ACLR is a topic that has been thoroughly investigated, with several studies comparing autograft options of the quadriceps tendon, patellar tendon, and hamstring tendon [4, 30, 33]. The hamstring autograft is a very commonly utilized option, with the benefits of having a greater load to failure compared with the patellar autograft and comparable short‐term and mid‐term clinical outcomes to the quadriceps tendon [35].…”
Section: Introductionmentioning
confidence: 99%
“…In some patients, the diameter of the final graft composed of the semitendinosus and gracilis tendons is below this threshold value, with some grafts being reported to be less than 7 mm [6]. Studies have proposed the utility of using anthropometric data such as height, weight, age, activity level and sex in order to predict graft size [33]. While anthropometric predictive models have been shown to be effective, it would be beneficial for surgeons to have a method to increase graft diameter in skeletally mature patients with smaller hamstring tendon grafts.…”
Section: Introductionmentioning
confidence: 99%